2018
DOI: 10.1038/s41598-018-33352-8
|View full text |Cite
|
Sign up to set email alerts
|

Beauvericin inhibits melanogenesis by regulating cAMP/PKA/CREB and LXR-α/p38 MAPK–mediated pathways

Abstract: Melanogenesis is the process of production of melanin pigments that are responsible for the colors of skin, eye, and hair and provide protection from ultraviolet radiation. However, excessive levels of melanin formation cause hyperpigmentation disorders such as freckles, melasma, and age spots. Liver X receptors (LXR) are nuclear oxysterol receptors belonging to the family of ligand-activated transcription factors and physiological regulators of lipid and cholesterol metabolism. In the skin, activation of LXRs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 45 publications
2
31
0
Order By: Relevance
“…In order to find effective natural compounds to treat melanoma, we investigated the cytotoxic effects in A375SM cells and the underlying molecular mechanisms of BEA and BEA G 1 , which are two fungal cyclic hexadepsipeptides. Previous studies have shown that BEA can induce apoptosis in several cancer cells, such as lung cancer, colon cancer, leukemia, and hepatoma cells [10][11][12][13][14]. However, there has been no report regarding the inhibitory activities of BEA and its analogue BEA G 1 against malignant melanoma.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to find effective natural compounds to treat melanoma, we investigated the cytotoxic effects in A375SM cells and the underlying molecular mechanisms of BEA and BEA G 1 , which are two fungal cyclic hexadepsipeptides. Previous studies have shown that BEA can induce apoptosis in several cancer cells, such as lung cancer, colon cancer, leukemia, and hepatoma cells [10][11][12][13][14]. However, there has been no report regarding the inhibitory activities of BEA and its analogue BEA G 1 against malignant melanoma.…”
Section: Discussionmentioning
confidence: 99%
“…The bioactive secondary metabolite beauvericin (BEA) was originally isolated from the entomopathogenic fungus Beaveria bassiana [10]. BEA, a cyclic hexadepsipeptide mycotoxin biosynthesized from N-methyl phenylalanine and 2-hydroxyisovaleric acid, is reported to exhibit diverse biological activities, including antimicrobial, insecticidal, antiviral, antiplatelet aggregation, ionophoric, anti-inflammatory, antimelanogenesis, and antitumor effects [11,12]. Mechanistic studies on the cytotoxic effects of BEA have shown that it induced apoptosis in several human cancer cells, such as those derived from the blood, lung, colon, liver, prostate, breast, pancreas, and brain.…”
Section: Introductionmentioning
confidence: 99%
“…Melanin content was determined as previously described by Lee et al [17]. Briefly, human epidermal melanocytes were treated with maclurin and then washed with PBS, harvested, and subjected to a melanin content assay.…”
Section: Assay For Melanin Contentmentioning
confidence: 99%
“…Maclurin concentration dependently increased both melanin content (Figure 1(b)) and cellular tyrosinase activity (Figure 1(c)) without any cytotoxicity at the concentrations tested (Figure 1(d)). In these experiments, forskolin was introduced as a positive control [17] because it increases both melanin content and cellular tyrosinase activity. In the Fontana-Masson staining and photography analysis, we found that maclurin treatment increased the level of melanin in the reconstructed epidermis (Figure 1(e)).…”
Section: Maclurin Promotes Melanogenesis In Human Epidermalmentioning
confidence: 99%
See 1 more Smart Citation